EFEKTIFITAS SIMPLISIA DAUN ALPUKAT (PERSEA AMERICANA MILL) DAN SIMPLISIA BIJI JINTAN HITAM (NIGELLA SATIVA) TERHADAP PENURUNAN TEKANAN DARAH - Risna Aulia (Jurnal Kesehatan, 2024)
Hypertension is a disease categorized as the silent killer disease because sufferers are unaware that they have hypertension. Herbal therapy is widely used by the community to manage hypertension because it has few side effects, such as avocado leaves and black cumin seeds. The purpose of this study was to determine the effectiveness of avocado leaf simplisia and black cumin seed simplisia in lowering blood pressure in hypertensive patients. This research was a True Experiment with a Nonequivalent Control Group Design, and a sample of 40 respondents was selected using purposive sampling technique. The results of blood pressure measurement effectiveness using the Wilcoxon test in four groups were as follows: avocado leaf simplisia group had a p-value of 0.0001, black cumin seed simplisia group had a p-value of 0.011, the group receiving both avocado leaf and black cumin seed simplisia had a p-value of 0.014, and the control group receiving the antihypertensive drug Amlodipine 10 mg had a p-value of 0.005. This means that avocado leaf simplisia was more effective compared to the other groups because the smaller the p-value, the more effective the administration of simplisia in reducing blood pressure. In conclusion, the administration of avocado leaf simplisia is more effective in lowering blood pressure, and it is recommended for hypertensive patients and the general public to consume avocado leaf simplisia not only to lower blood pressure but also because it has no side effects and is a herbal treatment.